AN ANALYSIS OF THE ABILITY OF THE SECOND YEAR STUDENTS OF SMAN 2 PANGKALAN KERINCI IN COMPREHENDING PROCEDURE TEXTS - Rohani Esterina Pasaribu; Fadly Azhar; Fakhri Ras (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The aim of this study is to find out the reading ability of the second year students of SMAN 2 Pangkalan Kerinci in comprehending procedure texts. The population of this research were all of the second year students which consisted of 253 students. There were 25 students who participated in this study. The instrument was a test adapted from authentic material. The frame of the test covers 8 components such as: finding main idea, finding factual information, finding meaning of difficult word, finding references, finding inferences, finding social function, finding generic structure, and finding language features. Each component consist of 4 question and for finding generic structure and language features consist of 3 question because the generic structure question and the language features is too difficult for the students. The test containing 30 items was used to collect the data. Before the test was administered, the test was tried out to find out the difficulty level and the reliability of the test. To analyze the data, the raw scores of the students were calculated and the level of ability was identified by using the classification of ability level by Harris (1974). The result showed that the ability of the second year students of SMAN 2 Pangkalan Kerinci in comprehending procedure texts was at Average to Good level with mean score 67. Therefore, it can be concluded that most of the students were able to comprehend procedure texts. However, the students are suggested to do more practice in reading procedure texts in order to comprehend procedure texts to improve the ability in reading due to the poorness of their reading ability.Key Words: Reading Ability, Reading Comprehension, Procedure Texts